A research on the radiation shielding effects of clay, silica fume and cement samples - Akbulut, Suat; Sehhatigdiri, Arvin; Eroglu, Hayrettin; Celik, Semet (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Nowadays, as the application areas of nuclear technology increases, protection from radiation has become even more important. Especially, the importance of radiation-shielding is important for the environment and employees which are in close proximity. Clays can be used as additives for shielding the radioactive materials. In this study, the shielding properties of micronize clay-white cement, clay-silica fume, gypsum, gypsum-silica fume, cement, white cement, cement-silica fume, white cement-gypsum, white cement-silica fume, red mud-silica fume, silica fume and red mud at different energy levels were examined. Additionally, compaction and unconfined compression tests were carried out on the samples. The results of clays and other samples were compared with each other. As a result, it was found that clays, especially clay-white cement mixture were superior than other samples in radioactive shielding. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Clay; Silica fume; Cement; Radiation Shielding; BUILDING-MATERIALS; CONSTRUCTION; Chemistry; Nuclear Science & Technology; Physics